2015
DOI: 10.1016/j.aqrep.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation among different morphotypes of the male freshwater prawn Macrobrachium rosenbergii (De Man)

Abstract: a b s t r a c tThe genetic differences between the blue claw male (BC), orange claw male (OC) and small male (SM) morphotypes of male freshwater prawns were assessed using microsatellite DNA markers. Thirty individuals from each of the three groups of male prawns were collected from a hatchery rearing system in Port Dickson, Negeri Sembilan, Malaysia. Significant differences in growth were observed between the three groups. The total numbers of alleles per locus in the BC, OC and SM groups were found to be 23,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Recent studies carried out in earthen ponds showed a significant additive genetic component for male morphotypes (Hung & Nguyen ; Banu et al . ). Selection for increased growth over four generations decreased the proportion of SM and increased the proportion of OC males in the selected population relative to control and did not change the frequency of the BC morphotypes in the population (Hung & Nguyen ).…”
Section: The Evolution Of Alternative Mating Tactics In the Genus Macmentioning
confidence: 97%
“…Recent studies carried out in earthen ponds showed a significant additive genetic component for male morphotypes (Hung & Nguyen ; Banu et al . ). Selection for increased growth over four generations decreased the proportion of SM and increased the proportion of OC males in the selected population relative to control and did not change the frequency of the BC morphotypes in the population (Hung & Nguyen ).…”
Section: The Evolution Of Alternative Mating Tactics In the Genus Macmentioning
confidence: 97%
“…Subordinate males have the potential to progress through caste, becoming larger prawn in the absence of a dominant male, which actively court and protect the females before mating (Barki et al, 1991; Karplus et al, 1991; Ra'anan & Cohen, 1985; Ra'anan & Sagi, 1985). Besides the social behaviour, the morphophysiological variations could be associated with genetic components and environmental conditions (Banu et al, 2015; Dinh & Nguyen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sexually mature males of GFPs develop through three distinct morphological types, namely blue claw males (BC), orange claw males (OC) and small males (SM), and they exhibit distinct heterogenous individual growth (HIG) (Aziz, Nguyen, Rahi, Hurwood, & Mather, 2017; Banu, Siraj, Christianus, Ikhsan, & Rajaee, 2015) (Figure 1). In addition to these three basic male morphotypes, another male morphotype—old blue claw males (OBC)—exists; OBC appear senescent, have an extremely developed second leg and carapace and have a low economic value (Dinh & Nguyen 2014) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of various male morphotypes of GFPs thus determines the economic benefits of farming. At present, although genetic variations among the three basic male morphotypes have been studied (Aziz et al., 2017; Aziz, Rahi, Hurwood, & Mather, 2018; Banu et al., 2015), the molecular mechanisms underlying growth differences among the various morphotypes remain unclear, and few studies have been conducted using OBC.…”
Section: Introductionmentioning
confidence: 99%